2013
DOI: 10.1016/j.jbiomech.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Vibration induced osteogenic commitment of mesenchymal stem cells is enhanced by cytoskeletal remodeling but not fluid shear

Abstract: Consistent across studies in humans, animals and cells, the application of vibrations can be anabolic and/or anti-catabolic to bone. The physical mechanisms modulating the vibration-induced response have not been identified. Recently, we developed an in vitro model in which candidate parameters including acceleration magnitude and fluid shear can be controlled independently during vibrations. Here, we hypothesized that vibration induced fluid shear does not modulate mesenchymal stem cell (MSC) proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 42 publications
9
99
2
Order By: Relevance
“…Therefore, our results regarding cell morphology and roughness should be treated as relative rather than absolute (Qian et al, 2010). Mechanical vibrations were shown to be anabolic for osteoprogenitor cell pools in vitro, whether the application of stimulus was vertical (Kim et al, 2012) or horizontal (Uzer et al, 2013). Our results were consistent with the increase in cell proliferation for quiescent stem cells, but we did not observe an increase in cell numbers of stem cells during osteogenic commitment, even though our results suggested increased viability.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, our results regarding cell morphology and roughness should be treated as relative rather than absolute (Qian et al, 2010). Mechanical vibrations were shown to be anabolic for osteoprogenitor cell pools in vitro, whether the application of stimulus was vertical (Kim et al, 2012) or horizontal (Uzer et al, 2013). Our results were consistent with the increase in cell proliferation for quiescent stem cells, but we did not observe an increase in cell numbers of stem cells during osteogenic commitment, even though our results suggested increased viability.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the idea that cytoskeletal elements are strong determinants of mechanotransductive pathways, chemical blocking of actin polymerization inhibits the response of bone cells to mechanical stimulation (Rosenberg, 2003). Similarly, molecular response to mechanical stimuli is augmented in progenitor cells during osteogenesis, when the treatment is combined with lysophosphatidic acid, an agent that induces rapid actin stress fiber formation (Uzer et al, 2013). Though cytoskeletal elements can guide the mechanical sensitivity of bone-forming cells during lowintensity vibrations, it is not clear whether cytoskeletal elements can adapt to this oscillatory stimulus, similar to adaptations observed in response to fluid shear (Malone et al, 2007;Ponik et al, 2007).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Because the vertical displacement of the vibrator at 60 Hz and 5 m/s 2 was 35 lm, this was too small to induce a horizontal flow. Therefore, it appears that the vibration-induced fluid shear stress acting on the cell layer in this study was less than that measured in Uzer's report (Uzer et al 2012(Uzer et al , 2013; (4) the maximum strain increased proportionally with peak acceleration (Fig. 4).…”
Section: Discussioncontrasting
confidence: 59%
“…We confirmed that there was no standing wave on the fluid surface within the range of accelerations and frequencies used in this study. Finite element methods revealed that the range of fluid shear stress placed upon the cell layer was 0.04-0.94 Pa (Uzer et al 2013) when the plate was horizontally vibrated (LMHF; 30-100 Hz, 0.98-9.81 m/s 2 ). Because the vertical displacement of the vibrator at 60 Hz and 5 m/s 2 was 35 lm, this was too small to induce a horizontal flow.…”
Section: Discussionmentioning
confidence: 99%